Epigenetic Aberrations in Mental Disorders are Linked to Diet and Gut Microbiome Alterations - Shabnam Nohesara; Hamid Mostafavi Abdolmaleky; Sam Thiagalingam (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
Nutrition and metabolism modify epigenetic codes such as histone methylation or acetylation and DNA methylation mediated by bioactive nutrients and gut microbial factors via influencing the gut–brain axis, which modulate neuronal activity and behavior. This chapter discusses epigenetic aberrations related to diet and gut microbiome alterations in major psychiatric diseases such as schizophrenia, bipolar disorder, and autism. Here, this study first discussed modifications to the structure and makeup of gut microbiome and their role in brain functional changes in serious mental illnesses. Afterwards, potential interactions among maternal diet, environmental factors, nutrition, and gastrointestinal microbiome, and their roles in the pathogenesis of mental illnesses via epigenetic changes were discussed. This study also provided an overview of the association between the gut microbiome, oxidative stress, and inflammation affecting epigenetic mechanisms. Additionally, this chapter presented underlying mechanisms which mediate the influence of gut microbiome, probiotics, and psychiatric drugs on mental health via microbiome-epigenetic modifications. Finally, it was concluded that disease pathogenesis is linked to changes in the microbiome structure/composition by perturbing the microbiome–gut-brain axis functions. Further research is needed to obtain greater insights on abnormally transmitted microbiomes on infant health, to mitigate the origins of neurodevelopmental diseases at early ages.